2014
DOI: 10.11622/smedj.2014067
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and visual outcome of traumatic paediatric cataract in suburban Malaysia: a ten-year experience

Abstract: METHODSWe conducted a retrospective study of 29 children below 17 years of age who were diagnosed with traumatic paediatric cataract and who attended Hospital Universiti Sains Malaysia, Kelantan, Malaysia, between January 2000 and December 2010. Follow-up periods ranged from 12 to 120 months. Demographic data, clinical features, mechanism and extent of injury, and final visual outcome were recorded. RESULTSThe study population was predominantly male. The right eye was injured in 62.07% of patients. A majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
3
10
0
1
Order By: Relevance
“…In the present study, male population was more affected than female population with a ratio of 2.85:1 as male are more involved in sports and outdoor activities. Similar results were obtained by Abdul Rahim Aldinaet al, Poonam N. Kalyanpadet al and Menon MN et al [6,7,8]. A majority of patients in the present study had traumatic cataract due to open globe injury (68%) as compared to closed group injuries (32%).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, male population was more affected than female population with a ratio of 2.85:1 as male are more involved in sports and outdoor activities. Similar results were obtained by Abdul Rahim Aldinaet al, Poonam N. Kalyanpadet al and Menon MN et al [6,7,8]. A majority of patients in the present study had traumatic cataract due to open globe injury (68%) as compared to closed group injuries (32%).…”
Section: Discussionsupporting
confidence: 90%
“…Better initial visual acuity has good final visual outcome. Ying Q et al, Abdul Rahim Aldina et al, Shah et al had similar results on initial visual acuity as predictive factor [13,6,17].…”
Section: Original Research Articlementioning
confidence: 70%
See 1 more Smart Citation
“…Similar results were found in a study conducted by Latif et al, where it was revealed that improvement in visual acuity was seen in 96% of children presenting in 3-5 years of age whereas only in 2% of cases presenting in 6-8 years of age 13 . In case of traumatic cataracts [14][15][16] , visual outcome was affected by the type of trauma. Most cases were of penetrating trauma where a corneal tear had been repaired in a prior surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Adlina AR et al also found corneal opacity to be the most common cause of decreased vision after surgery for traumatic cataract. 18…”
Section: Discussionmentioning
confidence: 99%